Three Decades of Atherosclerotic Reno-vascular Disease Management - Changing Outcomes in an Observational Study - Diana Vassallo; Darren Green; James Ritchie; Constantina Chrysochou; James Blunt; Philip A. Kalra (Karger Publishers, 2016)
Background/Aims: Optimized medical therapy has improved cardiovascular outcomes in the general population. To investigate whether changes in the management of atherosclerotic renovascular disease (ARVD) have had an impact on clinical outcomes. Methods: Recruitment into this single-center prospective cohort study started in 1986. Data was analyzed retrospectively. Patients were divided into four groups based on relationship of diagnosis year to landmark randomized controlled trials (RCT); group 1 - pre-large RCT data (1986-2000); group 2 - post-early RCT (2001-2004); group 3 - ASTRAL study recruitment era (2004-2009); group 4 - post-ASTRAL (2009-2014). Results: In total, 872 patients were followed for a median 54.9 months (IQR 20.2-96.2). Over successive time-periods, there was an increase in baseline utilization of renin angiotensin blockade (RAB) (group 4: 69% vs. group 1: 31%, pConclusions: Although fewer patients are being investigated for ARVD in our center, these have more cardiovascular comorbidities. Nonetheless, optimized medical therapy may have contributed towards improved proteinuria, renal function and clinical outcomes in patients diagnosed with ARVD.